Beneficial Results Obtained Applying A Zinc Regrind At The Magmont Concentrator - Arthur A. Schweizer (Society for Mining, Metallurgy & Exploration, 1981)
A method to improve the quality of Magmnt zinc concentrates to become acceptable feed to an electrolytic zinc refinery. The magnesia content of zinc concentrates produced was too high due to particle locking with the sphalerite in coarse fractions. Regrinding of the concentrates to a very fine particle size and then refloating the sphalerite was chosen to eliminate a sufficient amount of the magnesia to make the concentrates acceptable.